2020
DOI: 10.3390/antiox9050372
|View full text |Cite
|
Sign up to set email alerts
|

Do Antioxidant Vitamins Prevent Exercise-Induced Muscle Damage? A Systematic Review

Abstract: Free radicals produced during exercise play a role in modulating cell signaling pathways. High doses of antioxidants may hamper adaptations to exercise training. However, their benefits are unclear. This review aims to examine whether vitamin C (VitC) and/or vitamin E (VitE) supplementation (SUP) prevents exercise-induced muscle damage. The PubMed, Web of Science, Medline, CINAHL, and SPORTDiscus databases were searched, and 21 articles were included. Four studies examined the effects of acute VitC SUP given p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 66 publications
1
31
0
Order By: Relevance
“…Thus, while Nie and Lin [ 41 ] noted the reduced release of the muscle damage marker CK, both investigations were unsuccessful in reducing MS [ 36 ]. The findings of a review of the impacts of both VitE and VitC on exercise-induced muscle damage indicated that acute SUP may protect against muscle damage and improve recovery [ 45 ]. Despite this, we observed reductions in DOMS in those studies following a chronic SUP protocol before and after eccentric exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while Nie and Lin [ 41 ] noted the reduced release of the muscle damage marker CK, both investigations were unsuccessful in reducing MS [ 36 ]. The findings of a review of the impacts of both VitE and VitC on exercise-induced muscle damage indicated that acute SUP may protect against muscle damage and improve recovery [ 45 ]. Despite this, we observed reductions in DOMS in those studies following a chronic SUP protocol before and after eccentric exercise.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that some studies have evaluated the effects of vitamin E on the recovery of muscle contraction force following exercise. Overall, the available evidence on the effects of vitamin E alone or combined with vitamin C against exercise-induced muscle damage are not conclusive [ 3 ].…”
Section: Effects Vitamin E and C Supplementation: Environment Andmentioning
confidence: 99%
“…It has been estimated by the American College of Sports Medicine that approximately 50% of athletes take vitamin supplements with the goal of staying fit and improving endurance [ 1 , 2 ]. Recently, antioxidant supplementation has received attention among athletic populations as a possible method to reduce muscle damage incurred during exercise [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, it has been proposed that the intake of antioxidants could prevent exercise-induced muscle damage. In 2020, a systemic review concluded that there is some evidence of a protective effect of vitamin C and/or vitamin E supplementation against exercise-induced muscle damage (Martinez-Ferran et al, 2020).…”
Section: Discussionmentioning
confidence: 99%